Atropine-induced sinus tachycardia protects against exercise-induced ventricular arrhythmias in patients with catecholaminergic polymorphic ventricular tachycardia. Issue 4 (24th February 2020) - Kannankeril, Prince J; Shoemaker, M Benjamin; Gayle, Kathryn A; Fountain, Darlene; Roden, Dan M; Knollmann, Bjorn C
Abstract: Aims: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is an inherited arrhythmia syndrome characterized by exercise-induced ventricular arrhythmias, sudden death, and sinus bradycardia. Elevating supraventricular rates with pacing or atropine protects against catecholaminergic ventricular arrhythmias in a CPVT mouse model. We tested the hypothesis that increasing sinus heart rate (HR) with atropine prevents exercise-induced ventricular arrhythmias in CPVT patients. Methods and results: We performed a prospective open-label trial of atropine prior to exercise in CPVT patients (clinicaltrials.gov NCT02927223). Subjects performed a baseline standard Bruce treadmill test on their usual medical regimen. After a 2-h recovery period, subjects performed a second exercise test after parasympathetic block with atropine (0.04 mg/kg intravenous). The primary outcome measure was the total number of ventricular ectopic beats during exercise. All six subjects (5 men, 22–57 years old) completed the study with no adverse events. Atropine increased resting sinus rate from median 52 b.p.m. (range 52–64) to 98 b.p.m. (84–119), P = 0.02. Peak HRs (149 b.p.m., range 136–181 vs. 149 b.p.m., range 127–182, P = 0.46) and exercise duration (612 s, range 544–733 vs. 584 s, range 543–742, P = 0.22) were not statistically different. All subjects had ventricular ectopy during the baseline exercise test. Atropine pre-treatment significantly decreased the median number of ventricular ectopic beats from 46 (6–192) to 0 (0–29), P = 0.026; ventricular ectopy was completely eliminated in 4/6 subjects. Conclusion: Elevating sinus rates with atropine reduces or eliminates exercise-induced ventricular ectopy in patients with CPVT. Increasing supraventricular rates may represent a novel therapeutic strategy in CPVT.